A study of GGBS based cement concrete with the inclusion of waste foundry sand on mechanical properties. (2022) - Kumar Parashar, Arun; Sharma, Prashant; Sharma, Neha
Abstract: When GGBS is used as binder, strength of concrete will be examined, as will effect of adding waste foundry sand to the mix and how much GGBS should be used. The replacement percentages of 5, 10, 15, and 20 were used to make GGBS concrete samples for the M30 grade. 10 percent to 40 percent enhance in amount of waste foundry sand was incorporated into mix. The mechanical characteristics increased up to 15% GGBS replacement, but subsequently began to decline after that point. Flexural, compression, and split tensile strength of GC15 specimen were improved by 6.47 percent; 17.58 percent; and 12.84 percent after 28 days. The G15S30 sample's strength is increased by 7.68 percent, 16.15 percent, and 12.30 percent, respectively, when WSF is added. It became more difficult to work with the more GGBS there was in the mix. As a result, a blend of 30 percent WSF and 15 percent bagasse ash can be used to make an excellent bagasse ash concrete.